Analysis of The Allocation of Special Autonomy Funds in Infrastructure, Education and Health as The Areas With The Largest Allocation to Poverty Levels in Aceh - Glena Shafira Sebayang (Return : Study of Management, Economic and Bussines, 2023)
Aceh's poverty rate is still high enough to make Aceh the fifth poorest province in Indonesia. This is a concern because Aceh received additional transfer funds in the form of Special Autonomy Funds which are used for seven areas, namely, infrastructure maintenance and development, people's economic empowerment, poverty alleviation, education, social, health, and Aceh. However, of these seven areas, the areas that received the largest allocation were infrastructure, education, and health, while the other fields tended to get relatively small allocations. Nevertheless, infrastructure, education, and health continue to have an influence on poverty. For this reason, this study aims to determine how the influence of infrastructure, education, and health as fields that have a large allocation of funds in the Special Autonomy Fund on poverty levels. This study used panel data from 22 districts/cities in Aceh in the 2014-2021 research period. This study used regression panel fixed effect model data to see the estimated results. The results of this study show that the allocation of Special Autonomy Fund in infrastructure, education, and health has not significantly affected poverty rates in Aceh.